2019
DOI: 10.1002/cncr.32370
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in neurocognitive, emotional, and quality‐of‐life outcomes in survivors of childhood cancer: A report from the Childhood Cancer Survivor Study

Abstract: BACKGROUND: Survivors of childhood cancer are at risk of neurocognitive impairment, emotional distress, and poor health-related quality of life (HRQOL); however, the effect of race/ethnicity is understudied. The objective of this study was to identify race/ ethnicity-based disparities in neurocognitive, emotional, and HRQOL outcomes among survivors of childhood cancer. METHODS: Self-reported measures of neurocognitive function, emotional distress (the Brief Symptom Inventory-18), and HRQOL (the Medical Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…We must also consider the possibility of participation bias, both in the CTL and ALL groups, particularly regarding our evidence that full-scale IQ contributes to brain outcomes. While inclusion of the NIH neuroimaging repository mitigated some of this concern, innovative recruitment strategies are required for comprehensive investigation of neurocognitive late effects in ALL survivors ( Dixon et al, 2019 ). Additionally, we found that intracranial volume was significantly reduced in ALL survivors relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…We must also consider the possibility of participation bias, both in the CTL and ALL groups, particularly regarding our evidence that full-scale IQ contributes to brain outcomes. While inclusion of the NIH neuroimaging repository mitigated some of this concern, innovative recruitment strategies are required for comprehensive investigation of neurocognitive late effects in ALL survivors ( Dixon et al, 2019 ). Additionally, we found that intracranial volume was significantly reduced in ALL survivors relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Established risk factors for long‐term functional impairments include a brain tumor diagnosis, central nervous system (CNS)–directed chemotherapy and/or cranial radiation, younger age at diagnosis, and longer time since treatment 8‐11 . Some research, but not all, from our group and others suggests that CCSs from ethnic minority and/or lower socioeconomic backgrounds are at further risk for worse cognitive and health‐related quality of life (HRQOL) outcomes following cancer 12‐17 . The Hispanic population is now the largest ethnic or racial minority in the United States and it is estimated that Hispanic people will account for close to one‐third (29%) of the population by 2060 18 .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Some research, but not all, from our group and others suggests that CCSs from ethnic minority and/or lower socioeconomic backgrounds are at further risk for worse cognitive and health-related quality of life (HRQOL) outcomes following cancer. [12][13][14][15][16][17] The Hispanic population is now the largest ethnic or racial minority in the United States and it is estimated that Hispanic people will account for close to one-third (29%) of the population by 2060. 18 While social-ecological factors appear especially relevant for CCSs from socioeconomically disadvantaged groups, they have not been studied, despite the potential to inform tailored intervention approaches to improve outcomes.…”
mentioning
confidence: 99%
“…In the context of oncology, health disparities in the US are significantly different in the rates of cancer screening, incidence, survival, treatment-related complications, and quality-of-life (7). Although the 5-yr relative cancer survival rates of childhood cancer have reached 94% among the child and 85% among adolescent survivors (8), there is evidence of lower patient-reported outcomes and survival rates (9)(10)(11) in minority vs. non-Hispanic White survivors. Furthermore, the mechanisms behind these disparities are understudied.…”
Section: Introductionmentioning
confidence: 99%